KONSEP MAQASID SYARIAH DALAM PENGURUSAN WAKAF(MAQASID SHARIAH IN WAQF MANAGEMENT) (UMRAN - Journal of Islamic and Civilizational Studies, 2015)
This article will clarify the question of the Maqasid Shariah in waqf management. Basically, Islam strongly encourages infaq. One form of infaq is the waqf. An alternative for Muslims to infaq their property to the sabilillah, that is for the benefit of all beings. Allah putting maqasid shariah in every law of shariah. For this purpose, this article will explain on the waqf and its relation to Maqasid Shariah.
Keywords: Endowments; Maqasid Shariah; and Waqf Assets